The Iron Triangle of Energy: How to Improve Energy Cost, Reliability, and Emissions - Miller, Ronald L (River Publishers, 2024)
"The Iron Triangle of Energy" explores the intricate balance between cheap, reliable, and clean energy. In a world of trade-offs, this book provides rational ideas to optimize energy choices. With a focus on education and mentoring, it equips consumers, students, industry, and government with the knowledge needed to make informed decisions for our future. Rich with pertinent graphs, it offers a clear understanding of key energy issues.